The Influence of Leadership Styles/Behavior and Competencies Towards the Job Satisfaction of Employees in the Royal Malaysia Police - Navaretnam, Venugopal (2011)
This study is to identify the influence of leadership styles/behavior and competencies towards the job satisfaction of the police officers and men in the Royal Malaysia Police. This study is based on samples collected from Officers and Men of various units in the police force, particularly in the Management Departments of the Royal Malaysia Police Headquarters in Kuala Lumpur. This research also analyses the problems of motivation in the police force which has relative relationship between leadership styles or behaviour and their competencies. In this paper, the leadership style/behaviour was measured by the 20-item Leadership Style Questionnaire developed by Northouse (2001). This instrument has 10 items to measure task oriented leadership style and 10 items relational/people-oriented leadership style. Leaders’ competencies were measured by the Eight Universal Management and Leadership Competencies in 18 Skill Sets developed by the Profile Service Centre. This instrument contains three items to measure communication, three items for leadership, two items for adaptability, two items for relationships, two items for task management, two items for production, two items for development of others, and two items to measure personal development. Job satisfaction was measured by using the 5-item questionnaire developed by Brayfield and Rothe (1951).The findings revealed that leadership style and leaders’ competencies were significantly related to the overall job satisfaction. Moreover, it is found that competencies like communication skills, solving problems, listening effectively, processing information, motivating successfully, delegating responsibilities, building personal relationships, focusing on working efficiently, taking action, and achieving results have a significant effect on leaders.